2017
DOI: 10.1002/lary.26534
|View full text |Cite
|
Sign up to set email alerts
|

The repeatability of tests of eustachian tube function in healthy ears

Abstract: 3b. Laryngoscope, 127:2619-2626, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Two forms of ET function test were assessed as index tests: objective and semi-objective measures of ET opening, and symptom-based PROMS. Tests of ET opening for OETD (9 tests) and PETD (5 tests) were performed according to optimal methods previously identified[ 9 , 10 ] or standard procedure (PETD tests). Details of the tests of ET opening, their various methods and the repeats performed can be found in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two forms of ET function test were assessed as index tests: objective and semi-objective measures of ET opening, and symptom-based PROMS. Tests of ET opening for OETD (9 tests) and PETD (5 tests) were performed according to optimal methods previously identified[ 9 , 10 ] or standard procedure (PETD tests). Details of the tests of ET opening, their various methods and the repeats performed can be found in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…All participants underwent all OETD and PETD tests in a single session, with a single assessor (MS). Although previous work suggested fatigue and test interactions were minimal[ 10 ], the index tests were applied in a partly-randomised manner; tympanometry and the nine step test were always applied first to prevent residual middle ear pressure influencing results, while the order of the other tests was randomised using an online random sequence generator[ 14 ]. PROMs were also completed in a randomised order.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All participants underwent all tests in a single session, with a single assessor (M.E.S.). Although previous work suggested that fatigue and test interactions were minimal [Smith et al, 2017b], the index tests were applied in a partly randomised manner; tympanometry and the 9-step test were always applied first to prevent residual ME pressure influencing results, whilst the order of the other tests was randomised using an online random sequence generator. The PROMs were also completed in a randomised order.…”
Section: Et Function Testsmentioning
confidence: 99%